Medical residents’ consumption of psychoactive substances, bogotá, 2001 (2002)
A cross-sectional study was carried out to establish the prevalence of both legal and illegal psychoactive substance consumption in a population of medical and surgical resident students (193 subjects), from a university in Bogotá, and relate this to macro and micro social environmental factors. The instruments for data collection employed were the Epidemiological Surveillance System for Inadequate Use of Psychoactive Substances' (VESPA) questionnaire 1, and the alcohol consumption assessment scale (CAGE) to establish alcoholism and its risk. A 1% prevalence of illegal psychoactive substances was found and alcohol, coffee and cigarette consumption prevalence was 86.5%, 71.5% and 24.4%, respectively, which is similar to that found in the general population. The percentage of alcoholic students identified, according to the CAGE scale, was 5.2%, a much lower figure than that reported in other studies. The exploratory bi variable analysis was carried out by prevalence ratio; i.e. being aged between 24 and 28 years, being economically dependent on other people such as wife or husband, parents and/or brothers, having friends and relatives who get drunk and studying as a surgical resident were identified as risk factors for alcohol consumption to the point of drunkenness.